THE ROLE OF THE PRINCIPLES OF THE PROSECUTOR’S ACTIVITY IN ENSURING HUMAN RIGHTS AND FREEDOMS IN THE JUDICIAL PROCEEDINGS OF THE CRIMINAL PROCEEDINGS - PhD D.S.Dovudova (European Journal of Humanities and Educational Advancements, 2023)
In this article considers the concept of the principles of the criminal process, the principles of the prosecutor’s activities in the trial the concept, essence, theoretical aspects and the role of these principles in ensuring human rights and freedoms